Maternal Attainment of Exclusive Breastfeeding in Sampang Madura - Yunitasari, Esti; Paramida, Titin; Wahyudi, Andri Setiya (International Journal of Psychosocial Rehabilitation, 2020)
Exclusive breastfeeding is important to reduce death and pain rates among babies, which are high in Indonesia. Exclusive breastfeeding is still very low in Madura (38%). The aim of this research was to explain the factors related to maternal attainment of exclusive breastfeeding. This research was a cross-sectional study. Sampling was conducted using a purposive sampling technique. The instrument was a questionnaire which was tested for validity and reliability and given to 110 mothers who had babies aged 6-12 months in the working area of Sreseh Health Center, Sampang Regency. Most of respondents (59.09%) did not provide exclusive breastfeeding. Maternal attainment of exclusive breastfeeding was only in 19.09%; there was a relationship between family support, economic status, infant care, and health services (p=0.000) with maternal attainment of exclusive breastfeeding. Economic Status (x2=80,670 > 9,488) and health services (x2=41,594 > 5.99) had a strong relationship with maternal attainment of exclusive breastfeeding compared to other factors. Economic status and health care were the basis of improving maternal attainment of exclusive breastfeeding.